2018
DOI: 10.1038/s41598-018-29598-x
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual Temporal Processing in Postlingually Deafened Adults with Cochlear Implants

Abstract: For many cochlear implant (CI) users, visual cues are vitally important for interpreting the impoverished auditory speech information that an implant conveys. Although the temporal relationship between auditory and visual stimuli is crucial for how this information is integrated, audiovisual temporal processing in CI users is poorly understood. In this study, we tested unisensory (auditory alone, visual alone) and multisensory (audiovisual) temporal processing in postlingually deafened CI users (n = 48) and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Indeed, a number of fMRI studies in blind individuals have shown that in the absence of vision, visual cortex activation commonly associated with visual objects is utilized to encode sound objects (Amedi et al 2003;van den Hurk et al 2017;Vetter et al 2014). Similar recruitment of auditory areas and reweighting of visual cues has been found in deaf individuals and cochlear implant users (Benetti et al 2017;Bola et al 2017;Butera et al 2018). Overall, these studies demonstrate the brain's capacity for marked cross-modal plasticity, in which areas normally associated with one sensory modality can be influenced (and even taken over) by other sensory modalities.…”
Section: Neuroimaging and Far-field Recording: Neural Evidence For Cross-modal Modulation Of Auditory Processesmentioning
confidence: 90%
“…Indeed, a number of fMRI studies in blind individuals have shown that in the absence of vision, visual cortex activation commonly associated with visual objects is utilized to encode sound objects (Amedi et al 2003;van den Hurk et al 2017;Vetter et al 2014). Similar recruitment of auditory areas and reweighting of visual cues has been found in deaf individuals and cochlear implant users (Benetti et al 2017;Bola et al 2017;Butera et al 2018). Overall, these studies demonstrate the brain's capacity for marked cross-modal plasticity, in which areas normally associated with one sensory modality can be influenced (and even taken over) by other sensory modalities.…”
Section: Neuroimaging and Far-field Recording: Neural Evidence For Cross-modal Modulation Of Auditory Processesmentioning
confidence: 90%
“…This novel finding is noteworthy given that relatively little is known about low-level audiovisual stimulus detection in CI users (Stevenson et al 2017). However, based on our prior work, we do know that CI users' temporal judgments of synchrony for these same flashbeep stimuli are indistinguishable from controls in a simultaneity judgement experiment (Butera et al 2018). This suggests that low-level AV temporal function is likely intact in adult CI users, so any broader issues may be subtle.…”
Section: Discussionmentioning
confidence: 91%
“…(which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. (Butera et al 2018). This suggests that low-level AV temporal function is likely intact in adult CI users, so any broader issues may be subtle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were not diagnosed with psychiatric or neurological disorders, as assessed by a short questionnaire at inclusion in the study. The control participants were selected for their hearing-in-quiet capacities rather than their age, leading to age differences between the groups [ 20 , 69 , 90 ]. As age-difference could have played a role in the CI results, we performed Pearson correlations between each score obtained in the Results section and the age of the CI users, with Bonferroni correction for multiple testing.…”
Section: Methodsmentioning
confidence: 99%